CONSUMER AUTONOMY AND ALGORITHMIC CONTROL: NETFLIX AS A DIGITAL BROADCASTING ALTERNATIVE IN THE GLOBAL MARKETPLACE - Muhamad Agung Dharmajaya; Aminah Swarnawati (GoAcademica Research dan Publishing, 2026)
This study explores the tension between consumer freedom and control. algorithmic use of the Netflix streaming platform. The research employs a literature review methodology, using sources from Google Scholar to investigate the impact of recommendation algorithms on user autonomy and content consumption patterns. Specifically, it focuses on Netflix's collaborative filtering algorithms, binge-watching phenomena, and the tension between consumer freedom and platform-driven content selection. Findings reveal that while Netflix promotes personalized recommendations, these algorithms often lead to repetitive consumption patterns and reinforce specific cultural perspectives. Furthermore, the platform's business model, emphasizing user retention and engagement through continuous consumption, fosters behavioral dependencies like binge-watching. The study highlights that although Netflix offers mechanisms for content personalization, such as “Play Something Else,” these tools subtly shift control to the algorithm, reducing consumer autonomy. Conclusions suggest that Netflix's use of algorithmic control reflects broader trends in digital media consumption, where the promise of user freedom is moderated by the platform's operational logic, prioritizing engagement and profit. These findings underscore the need for critical awareness of how algorithmic systems influence consumption and the balance between consumer freedom and algorithmic governance in streaming services.